2018
DOI: 10.15295/bmij.v6i3.317
|View full text |Cite
|
Sign up to set email alerts
|

Algilanan Örgütsel Adaletin Örgütsel Si̇ni̇zm Üzeri̇ne Etki̇si̇: Algilanan Örgütsel Desteğin Aracilik Rolü

Abstract: In this study, it is aimed to investigate the mediating role of perceived organizational support on the effect of organizational justice perceptions of employees on organizational cynism. Data of the research collected via online questionnaires from 518 police officers who are working in Turkish Police Organization. Participants of the sample group is adequate to represent the research population. In the study, questionnaire technique used for gathering the data. Construct validity of the scales was tested wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…In comparison with previous research, it has been found similar results. For example, in a research by Kanbur & Canbek (2018), the effect of organizational justice on organizational cynicism was examined in 530 police officers. The results of the study showed that there was a negative correlation between these variables.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with previous research, it has been found similar results. For example, in a research by Kanbur & Canbek (2018), the effect of organizational justice on organizational cynicism was examined in 530 police officers. The results of the study showed that there was a negative correlation between these variables.…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde bu alanda yapılan benzer çalışmalarda da örgütsel adalet algısı ile örgütsel sinizm arasında negatif yönde anlamlı ilişki olduğu sonuçlarına ulaşılmıştır (Kılıç & Toker, 2020;Korkmaz & Ünüvar, 2019;Kanbur & Canbek, 2018;Efeoğlu & İplik, 2011). Öğretmenler üzerinde bu konuda yapılan bir çalışmada öğretmenlerin örgütsel adalet algıları ile örgütsel sinizm düzeyleri arasındaki ilişki ele alınmış, çalışmada söz konusu değişkenler arasında negatif yönde anlamlı bir ilişki olduğu, bu bağlamda öğretmenlerde örgütsel adalet algısı yükseldikçe örgütsel sinizm düzeyinin düştüğü tespit edilmiştir (Şamdan & Atanur-Baskan, 2019).…”
Section: Discussionunclassified
“…Out-group's behavior toward in-group can be taken as sarcastic thus; observed organizational support would avoid employees from being in sarcastic to others (Kanbur and Canbek, 2018). Another study by Ergün and Eyisoy, (2018) demonstrated that providing an opportunity to team members for improvement increased the team's cooperation.…”
Section: Recommendations and Limitationsmentioning
confidence: 99%